Viabilidade do ambiente de contratação livre em um órgão público - Trindade, Humberto de Oliveira (2020)
This work has as purpose to demonstrate the study about economic viability for reduction of associated costof energy from Brazilian public agents through the migration from Regulated Contract Environment into Free Contract Environment. Aiming to sustainability and exchequer reasonableness, it was sought an expressive economy on cost. The purely technological methods have been already exhaustively explored, remaining an approach in the current legislation. The methodology research used the direct verification of field with sources of relevant information as Federal Universities, that have Electrical Engineering in their Graduation Courses, as well as Energy Traders. The data collection was realized quantitatively through emails, direct personal contact with people from these areas, visits in specialized sites as well as na accurate research in academic bibliografic materials. On this way the research coverd the University scenario and scenario of others public agencies. The research limitation was to be carried out in the theoretical field and future works that demonstrate the practicality of this study will be important. As contribution it brings a case study with the Federal University of Santa Maria, withcurrent data on the consumption in theinstitution as in Brazilian scenarios. In the result are presented the calculations of attractiveness, using indexes used by Federal Public Administration and, finally, in conclusion, the opinion that Free Contract Environment is a better option.